DOI: 10.3990/1.9789036546348
|View full text |Cite
|
Sign up to set email alerts
|

Independent aging with the help op smart technology : investigating the acceptance of ambient assisted living technologies

Abstract: Acknowledgements Curriculum Vitae 12 MEET CHARLES Meet Charles Charles is a retired tax advisor. Since his wife passed away last year, he has been living alone. Charles was always engaging in a lot of different activities together with his wife, but without his companion he simply lacks the motivation and energy to leave the house a lot. Except for his diabetes, Charles was always pretty healthy but since he stopped being active his physical health has deteriorated. His only daughter Anne lives an hour away fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 254 publications
(686 reference statements)
0
10
0
1
Order By: Relevance
“…Participants were presented with a short (2.25 minutes) video animation that explained the concept of AAL [ 65 ]. Previous research has shown that animated content with spoken text works well to communicate complex health-related information [ 66 ].…”
Section: Methodsmentioning
confidence: 99%
“…Participants were presented with a short (2.25 minutes) video animation that explained the concept of AAL [ 65 ]. Previous research has shown that animated content with spoken text works well to communicate complex health-related information [ 66 ].…”
Section: Methodsmentioning
confidence: 99%
“… 3 Personal innovativeness The willingness of persons to try out new ICT. 4 The questions have been adapted from existing questionnaires [ 29 , 30 ] …”
Section: Methodsmentioning
confidence: 99%
“…The constructs included based on the UTAUT were: Intention to use ( n = 3), Outcome expectancy (n = 3), Effort expectancy ( n = 4), Attitude (n = 4), Social influence (n = 3), Facilitating conditions (n = 4), Anxiety ( n = 3) and Self-efficacy ( n = 3). Another validated construct about Personal innovativeness (4 items) based on DOI was added [ 27 , 30 , 31 ]. The wording of individual items were adapted to fit the research focus on video communication in terminal care.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations